The impact of AI- assisted language learning tools on augmenting university EFL students’ speaking skills in Jordan (Journal of Applied Learning and Teaching, 2025)
This study aims to investigate the effect of the ELSA speech analyzer application, an artificial intelligence platform, on developing the speaking skills of English as a Foreign Language (EFL) students. The participants encompassed 34 university EFL students who were randomly assigned to either an experimental group or a control group. The students in the experimental group received instruction and assessment utilizing the ELSA speech analyzer application, while those in the control group were taught using traditional methods, specifically rubrics. Data were collected through the application of both the AI tool and rubrics. The findings indicated that the experimental group outperformed the control group in overall speaking skills and in all standards of speaking, including pronunciation, intonation, fluency, vocabulary, and grammar. Based on these results, it is essential to incorporate AI tools into university course descriptions and the teaching and assessment processes. Moreover, tutors should receive professional development training on efficiently employing AI applications like ELSA to maximize their potential in engaging students through interactive tasks, personalized real-life activities, and adapting course content to align with AI tools. Additionally, it is crucial to enhance students’ use of AI applications in learning English, particularly in speaking, and to evaluate students’ speaking skills through AI platforms.